Analysis of the application of the contentious and contentious-administrative process in the legislation and jurisprudence of the Bolivian Agro-environmental Court - Villalta Villarpando, Nicole Daiana (2024)
The present work, intends to approach a contrasted study about the application of the contentious and contentious-administrative process based on its close relationship with the national legislative evolution in Bolivia, as well as, the faculties attributed to the Agro-environmental Court for the review and resolution of this process from the jurisprudence issued in agrarian matters; under the main focus of the investigative development to the judicial actions against sanitation resolutions. The treatment of this topic deserves to be considered for its theoretical contribution that translates into a better understanding of this process for its correct application in the field of jurisdictional action. Likewise, the limitations and challenges of the process in question are discussed, adding the need to clarify the legislation and consistency of its application in reorganization resolutions. Also, the importance of the jurisprudence in the differentiation of the contentious process and the administrative contentious process, and the need to examine whether the administrative acts were carried out within the margins of the regulations governing such processing. Therefore, this study provides a detailed perspective on a crucial aspect of the judicial system, offering insights that can improve legal practice in this field.